The evolution of operative access in lung surgery - Aleksei Vladimirovich Mikheev; Sergey Nikolaevich Trushin; Aleksandr Yurievich Ogoreltsev (Termedia Publishing House, 2022)
In modern surgical practice, considerable attention is paid to reducing surgical trauma and reducing the incidence of postoperative complications, which has a direct impact on the duration of hospitalization and patient recovery. In chest surgery, this problem is most significant, since to perform small interventions on the lungs and pleura, a wide thoracotomy was required with the transection of the chest muscles and the separation of the ribs. The article describes modern minimally invasive approaches used in lung surgery. Particular attention is paid to the role of video-assisted surgical interventions in the surgical treatment of non-small cell lung cancer. The results of traditional multiport thoracoscopic lung resections were compared with standard open thoracotomy. The advantages and possible disadvantages of various options for video-assisted surgical interventions on the lungs are described.